Cognitive Neuroscience Robotics A Synthetic Approaches to Human Understanding - Kasaki, Masashi; Ishiguro, Hiroshi; Asada, Minoru; Osaka, Mariko; Fujikado, Takashi; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2016)
Cognitive Neuroscience Robotics is the first introductory book on this new interdisciplinary area. This book consists of two volumes, the first of which, Synthetic Approaches to Human Understanding, advances human understanding from a robotics or engineering point of view. The second, Analytic Approaches to Human Understanding, addresses related subjects in cognitive science and neuroscience. These two volumes are intended to complement each other in order to more comprehensively investigate human cognitive functions, to develop human-friendly information and robot technology (IRT) systems, and to understand what kind of beings we humans are. Volume A describes how human cognitive functions can be replicated in artificial systems such as robots, and investigates how artificial systems could acquire intelligent behaviors through interaction with others and their environment.
Compliant Body as a Source of Intelligence -- Motor Control Based on the Muscle Synergy Hypothesis -- Motor Control Based on the Muscle Synergy Hypothesis -- Mirror Neuron System and Social Cognitive Development -- Attention and Preference of Humans and Robots -- Communication for Social Robots -- System Evaluation and User Interfaces -- Robotics for Safety and Security -- Android Science.
Keywords: Control engineering; Robotics; Automation; Artificial intelligence; Computational intelligence; Neurosciences; Control, Robotics, Automation; Artificial Intelligence; Computational Intelligence; Neuroscience